Debris-carrying camouflage among diverse lineages of Cretaceous insects - Wang, Bo (Sci Adv, 2016)
Insects have evolved diverse methods of camouflage that have played an important role in their evolutionary success. Debris-carrying, a behavior of actively harvesting and carrying exogenous materials, is among the most fascinating and complex behaviors because it requires not only an ability to recognize, collect, and carry materials but also evolutionary adaptations in related morphological characteristics. However, the fossil record of such behavior is extremely scarce, and only a single Mesozoic example from Spanish amber has been recorded; therefore, little is known about the early evolution of this complicated behavior and its underlying anatomy. We report a diverse insect assemblage of exceptionally preserved debris carriers from Cretaceous Burmese, French, and Lebanese ambers, including the earliest known chrysopoid larvae (green lacewings), myrmeleontoid larvae (split-footed lacewings and owlflies), and reduviids (assassin bugs). These ancient insects used a variety of debris material, including insect exoskeletons, sand grains, soil dust, leaf trichomes of gleicheniacean ferns, wood fibers, and other vegetal debris. They convergently evolved their debris-carrying behavior through multiple pathways, which expressed a high degree of evolutionary plasticity. We demonstrate that the behavioral repertoire, which is associated with considerable morphological adaptations, was already widespread among insects by at least the Mid-Cretaceous. Together with the previously known Spanish specimen, these fossils are the oldest direct evidence of camouflaging behavior in the fossil record. Our findings provide a novel insight into early evolution of camouflage in insects and ancient ecological associations among plants and insects.